Structural, electronic, and elastic properties of orthorhombic, hexagonal, and cubic Cu3Sn intermetallic compounds in Sn–Cu lead-free solder. (March 2020) - Qu, Deyi; Li, Caiju; Bao, Longke; Kong, Zhuangzhuang; Duan, Yonghua
Abstract: In order to obtain a better understanding of the phase stabilities and mechanical behaviors of Cu3 Sn compounds, we performed first-principles calculations to predict the structural, electronic, and elastic properties of orthorhombic, hexagonal, and cubic Cu3 Sn compounds in Sn–Cu lead-free solder. The phase stabilities of these Cu3 Sn intermetallic compounds were investigated based on their formation enthalpy and cohesive energy, and the results indicated that the phase stabilities of the Cu3 Sn intermetallic compounds follow the order of: o -Cu3 Sn- Cmcm > o -Cu3 Sn- Pmmn > h -Cu3 Sn > c -Cu3 Sn, where c -Cu3 Sn is energetically unstable. The density of states, charge density difference, and atomic Mulliken charge were calculated to identify the characteristics of the chemical bonds. The single-crystal elastic constants and polycrystalline elastic moduli were obtained, and the elastic anisotropy was then assessed based on the elastic anisotropy index and factor, three-dimensional surface, and planar projection. The results indicate that the Cu–Sn bonds are covalent and that the Cu–Cu bonds are metallic-ionic mixed. The elastic anisotropy results follow the order of: c -Cu3 Sn > h -Cu3 Sn > o -Cu3 Sn- Pmmn > o -Cu3 Sn- Cmcm . Highlights: c -Cu3 Sn is energetically unstable and mechanically unstable. Cu–Sn bonds are covalent, whereas Cu–Cu bonds are mixed metallic–ionic. Elastic anisotropy determined as: c -Cu3 Sn > h -Cu3 Sn > o -Cu3 Sn- Pmmn > o -Cu3 Sn- Cmcm.